2020
DOI: 10.1021/jacs.0c00524
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed sp3 C–H Borylation in Hydrocarbon Solvent Enabled by 2,2′-Dipyridylarylmethane Ligands

Abstract: Iridium-catalyzed alkane C−H borylation has long suffered from poor atom economy, resulting from both the inclusion of only 1 equiv of boron from the diboron reagent and a requirement for neat substrate. An appropriately substituted dipyridylarylmethane ligand was found to give highly active alkane borylation catalysts that facilitate C−H borylation with improved efficiency. This system provides for complete consumption of the diboron reagent, producing 2 molar equivalents of product at low catalyst loadings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 31 publications
(87 reference statements)
5
49
0
Order By: Relevance
“…[16][17] Additionally, cyclometalation of the aryl ring under the reaction conditions would allow for the use of the same pre-catalysts previously found to be effective in diimine systems. As we recently reported, 15 we found that while the dipyridylphenylmethane ligand L1, does give an active catalyst for n-octane borylation, it significantly underperforms the benchmark Me4Phen/Ir system ( Figure 4). As part of an effort to examine the fate of the ligand during catalysis, we prepared the fluorinated derivatives L2 and L3.…”
Section: Ligand Systems For Iridium-catalyzed Sp 3 C-h Borylationsupporting
confidence: 77%
See 4 more Smart Citations
“…[16][17] Additionally, cyclometalation of the aryl ring under the reaction conditions would allow for the use of the same pre-catalysts previously found to be effective in diimine systems. As we recently reported, 15 we found that while the dipyridylphenylmethane ligand L1, does give an active catalyst for n-octane borylation, it significantly underperforms the benchmark Me4Phen/Ir system ( Figure 4). As part of an effort to examine the fate of the ligand during catalysis, we prepared the fluorinated derivatives L2 and L3.…”
Section: Ligand Systems For Iridium-catalyzed Sp 3 C-h Borylationsupporting
confidence: 77%
“…As we recently reported, 15 we found that, although the dipyridylphenylmethane ligand L1 did give an active catalyst for n-octane borylation, it significantly underperformed the benchmark Me 4 phen/Ir system (Scheme 3). As part of an effort to examine the fate of the ligand during catalysis, we prepared the fluorinated derivatives L2 and L3.…”
Section: Figure 1 Postulated Binding Modes For Various Ligands For Sp 3 C-h Borylationsupporting
confidence: 65%
See 3 more Smart Citations